An evaluation of bible and theological school libraries belonging to PABATS - Villareal, Ma. Nora A. (Institute of Library Science, University of the Philippines Diliman, 1996)
This study was conducted to determine the present status of libraries of Philippine Association of Bible and Theological Schools (PABATS) and also to find out if these Bible and Theological Schools libraries belonging to PABATS conformed to its own standards which are ready for accreditation and which are not. Self-evaluation Questionnaire was the principal instrument used for gathering the data, follow-up interviews were also made.